СЦЕНИЧЕСКОЕ РЕЧЕВОЕ ИСКУССТВО В КОНТЕКСТЕ СОЦИАЛИСТИЧЕСКЛГО РЕАЛИЗМА: ЛОГИКО-СТИЛИСТИЧЕСКИЕ КАНОНЫ - Prokopowa, Natalia (Przegląd Rusycystyczny, 2016)
Sceniczna sztuka słowa w kontekście realizmu socjalistycznego: kanony logiczno-stylistyczne aktualność refleksji nad sceniczną sztuką słowa okresu sowieckiego wynika z braku wyczerpujących badań na ten temat. autorka stawia sobie za cel zrekonstruowanie kanonów logiczno-stylistycznych działających w tym okresie w socrealistycznych wzorcach scenicznej sztuki słowa. za materiał do badań posłużyła oficjalna sowiecka sztuka słowa badana z perspektywy kulturowo-historycznej, zaś podstawą metodo-logiczną stała się wypracowana wcześniej przez autorkę typologia publicznej kultury słowa.autorka twierdzi, że sceniczna sztuka słowa oficjalnej sowieckiej kultury przynale-ży do typu retorycznego. w pracy zostaje nakreślona analogia pomiędzy ogólnymi regułami realizmu socjalistycznego, aksjologicznymi horyzontami scenicznej sztuki słowa oraz jej technologicznymi kanonami. zgodnie z celami pracy zostały opisane i uzasadnione te technologiczne kanony, które związane są z logika i stylem sztuki słowa. autorka definiuje znaczenie pojęcia kanonu w odniesieniu do scenicznej sztu-ki słowa i uzasadnia oddziaływanie na nią dwóch tego rodzaju kanonów: „priorytetu tekstu” oraz „ilustratywności”. uzasadniając owe kanony, autorka odwołuje się do badań lingwistycznych, koncentrujących uwagę na związлг leksyki, składni i brzmią-cej ze sceny mowy. Stage speech art in the context of the socialist realism:logical-stylistic canons the object of the article is stage speech art, which belongs to the official branch of soviet culture. the author explains the urgency of the comprehension of the stage speech art of soviet period by the absence of scientific reflection of this question and by the timeliness of its reconsideration. the previously developed by the author typology of public speech culture is used as the methodological support of this re-search. this typology obtains confirmation of belonging with the rhetorical type of the stage speech art of the official branch of soviet culture in the article.the purpose of the article is formulation of logical- stylistic canons of stage speech art of the official branch of soviet culture. the principles of socialist realism and the value installations of stage speech art are analyzed here. the possibility of applying the value installations of stage speech art as the criteria of the identification of rhe-torical type models is argued. the correspondence between the general principles of socialist realism, the value installations of stage speech art and its technological canons is established in the publication. the author determines the meaning of the term “canon” in connection with to stage speech art, he establishes and bases the technological canons, connected with logic and style of stage speech art, argues the action of two logical- stylistic canons: “the priority of text” and “illustrative quality”. the results of studies of linguists are used for the substantiation of the logical- sty-listic canons of stage speech art. there is an accent on the connection of vocabulary, syntax and stage speech.the article testifies to early forming of canon “priority of text”, explained the prin-ciple of its realization in the stage speech art. the author gives special attention to the argumentation of the canon “illustrative quality”. the technology of the applica-tion of an illustrative approach in the process of the stage embodiment of author’s text is revealed in the article. author proves the presence of the connection between using of simple speech tasks in the process of the work with the text and illustrative style in the stage speech art.